Analysis Of Implementation Planning Program Delivery And Prevention Of Complications ( P4K ) In Preparing Candidate Blood Donors Ready For Use By Village Midwives District Pekalongan - Nur Hidayati (Universitas Muhammadiyah Ponorogo, 2019)
P4K is an activity that facilitated Posted midwife Frame hearts improve Active Role husband, family and 'community planning hearts delivery Safe And Preparing for the possibility of complications hearts with AKI Lowering purposes. Pekalongan occupy sequence number seven the highest maternal mortality rate in Central Java. The second most common cause of death of 28% because bleeding occurred. By line P4K The Government then announced its ranks Along Pekalongan Pekalongan cooperate with PMI. In Order to Accelerate the decline in MMR and IMR with facilitate and provide 5 Candidate Ready For Blood wati 1 Asking pregnant / Maternity. Implementation progressed wati Candidate Preparation Blood For The Mother Maternity prayer depending on Human Resources. Wherewith the amount of research is qualitative with depth Interviews To the midwife Active and Inactive AS Key informant. That informant triangulation Head of Puskesmas, Kader Health, Pregnancy, and Donors. by data analysis techniques Content analysis.Research that implementation Preparation of Prospective Blood wati Ready Mix It Runs in Small portion midwife.It is advisable to review boost between Cooperation Department of Health, Red Cross, health centers, midwives and community leaders hearts dissemination activities. There penetapaan Implementation Procedures, reward For The village midwife carry out telecoms.